Development of unicycle mobile robot - Mohd Zamzuri Ab Rashid (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
Unicycle mobile robot's main advantage over multi-wheeled mobile robot is its higher degree of mobility. However, the system is inherently unstable and poses many interesting challenges especially in the modeling and control of the system. In this research work, the goal is to develop a unicycle mobile robot platform that is able to stabilize its posture upright with the help of a dedicated controller. The robot was developed and made of two parts namely, the lower and the upper parts. The lower part constitutes an active wheel, which is capable to move back and forth in order to stabilize the pitch orientation of the system. Meanwhile, the upper part of the robot consists of a reaction disc and main frame, which is used to stabilize the roll orientation of the unicycle mobile robot. From the abstraction of the system, the mechanical design was drafted by using the AutoCAD software and the physical body of the robot was developed by using various machining techniques and materials. Some important parameters have been gathered from the physical platform of the robot in order to be used in the analytical modeling of the robot. The analytical model of the unicycle mobile robot was developed by using Euler-Lagrangian approach and the dynamic equation derived was verified by using Newtonian approach. The analytical model was simulated extensively by using MATLAB software and the dynamics were compared to the real open loop performance of the system. The results reflect certain similarity. The research then proceeded to the design of the system controller where the model is first linearized by using Jacobian matrix. The goal of the controller is to stabilize the posture of the unicycle mobile robot to stay upright. In particular, a Linear Quadratic Regulator (LQR) was designed to stabilize the roll and pitch angles of the robot. The performance of the controller has been investigated thoroughly via simulation and experimental study. The results from the simulation study show that the unicycle mobile robot can be stabilized by using LQR controller by assuming the roll and the pith angles to be closed to zero. Through a series of experimental study, it was shown that that the real unicycle mobile robot was also able to move and stabilize the upright posture.